Structure and Performance: The Task of Economic History - North, Douglass C.; Anderson, Terry; Barzel, Yoram; Borcherding, Tom; Case, Elisabeth; Cheung, Steven N. S.; Goldberg, Victor P.; Higgs, Robert; Silberberg, Gene (Journal of Economic Literature, 2016)
JHE CLIOMETRIC revolution in ecoknomic history wedded neoclassical economics and quantitative methods in order to describe and explain the performance of economies in the past.' Economic history gained in rigor and scientific pretension, but at the expense of exploring a much more fundamental set of questions about the evolving structure of economies that underlies performance.2 Cliometricians have turned their backs on a long tradition stretching back from Joseph Schumpeter to Karl Marx to Adam Smith. These scholars regarded economic history as essential because it added a dimension to economics. Its purpose was to analyze the parameters held constant by the economist. If economics is a theory of choice subject to specified constraints, a task of economic history was to theorize about those evolving constraints. The failure of economic historians to provide their colleagues with a historical dimension to their perspective has reduced the effectiveness of economists in dealing with contemporary problems. Failure of economists to appreciate the transitory character of the assumed constraints and to understand the source and direction of these changing constraints is a fundamental handicap to further development of economic theory. The challenge to the economic historian which has equally compelling implications for the economic theorist is to explain the transformation of the structure of the American Economy in the past century.3 In the rest of this essay I shall explore this issue in order to specify some of the dimensions of the economic historian's task.